1999
DOI: 10.1159/000015959
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Vasoreactivity of the Basilar Artery System in Patients with Brainstem Lacunar Infarcts

Abstract: Background and Purpose: Diminished vasoreactivity (VR) has been evidenced in patients with hemispheric small vessel disease, however, there is no data regarding vertebrobasilar (VB) territory VR changes in patients with subcortical vascular encephalopathy located in the brainstem. Therefore, we compared the cerebral blood flow velocity (CBFV) responses of the VB system during different vasoregulatory challenges in healthy volunteers to those in patients with brainstem lacunar infarcts. Methods: In 20 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…As highlighted throughout this review, numerous efforts have been made to establish normal criteria for CO 2 reactivity of the cerebral circulation by the use of TCD. Although there has been ample research involving normal values for the anterior half of the circle of Willis, mainly for the MCA, we have found few studies involving these values for the basilar artery (19,67,80,96,139,148,154). Nonetheless, these studies seem to support the notion that MCAv measurement is likely to reflect blood flow in the region(s) of the central chemoreceptors.…”
Section: Methodological Considerations For the Integrated Assessment mentioning
confidence: 78%
“…As highlighted throughout this review, numerous efforts have been made to establish normal criteria for CO 2 reactivity of the cerebral circulation by the use of TCD. Although there has been ample research involving normal values for the anterior half of the circle of Willis, mainly for the MCA, we have found few studies involving these values for the basilar artery (19,67,80,96,139,148,154). Nonetheless, these studies seem to support the notion that MCAv measurement is likely to reflect blood flow in the region(s) of the central chemoreceptors.…”
Section: Methodological Considerations For the Integrated Assessment mentioning
confidence: 78%
“…[22][23][24][25][26][27] For example, Molina et al 24 found a significantly lower cerebrovascular reactivity (CVR) in patients with lacunar strokes, and Bakker and colleagues 25 found a strong association between impaired vasomotor reactivity and periventricular white matter lesions. In addition, Panczel and colleagues 26 reported impaired basilar artery CVR in patients with brainstem lacunar strokes compared with healthy volunteers and attributed this finding to microangiopathy within the brainstem. Puls et al 27 demonstrated the use of TCD arteriovenous cerebral transit time measurements to evaluate the cerebral microcirculation, finding substantially prolonged transit times in patients with vascular dementia compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Most papers excluded patients with carotid stenosis (except 1 30 ), 5 excluded cardiogenic sources of emboli, 32,33,36,38,41 and 3 excluded middle cerebral artery (MCA) stenosis 35,39,40 from the lacunar stroke group.…”
Section: Characteristics Of Included Patients and Control Subjectsmentioning
confidence: 99%